Capital-goods imports and US growth - Michele Cavallo; Anthony Landry (Bank of Canada, 2018)
Capital-goods imports have become an increasing source of growth for the U.S. economy. To understand this phenomenon, we build a neoclassical growth model with international trade in capital goods in which agents face exogenous paths of total factor and investment-specific productivity measures. Investment-specific productivity measures are reflected by the price of capital-goods imports, the price of domesticequipment investment, and the price of IP products relative to the price of consumption. We use observed prices to solve for optimal investment decisions, and understand the underlying sources of output growth in the U.S. economy. Our findings suggest that the model allocation decisions coming from changes in relative prices explain well the dynamics of investment and U.S. output. Using the model economy, we show that: (i) capital-goods imports have contributed 14 percent to growth in U.S. output per hour since 1975, (ii) capital-goods imports played a small role in the recent weakness in equipment investment, (iii) U.S. output-per-hour growth could have been 18 percent lower without the capital-goods imports technology since 1975, and (iv) in the long run, the implementation of additional tariffs on capital-goods imports would have little impact on the expenditure share of capital-goods imports in equipment investment.
Keywords: E2; F2; F4; O3; O4; 330; Productivity; Trade integration